A Study on Patients with TB and HIV Co-Infection in Relation to Mean CD4 Counts - M, Neethi Chandra; TS, Durga Prasad; Devulapalli, Meghana; Shaik, Shabana Banu; Bondalapati, Avanthi; Bathula, Pavan Kumar (Indian Journal of Pharmacy Practice)
Aim: To study the presentation of HIV-TB co-infection, co-relating the mean CD4 counts with regard to age and gender of the affected individuals. Methodology: A cross-sectional study on a total of 334 HIV positive patients diagnosed with tuberculosis was performed and individuals with age more than or equal to 18 years were selected. The data available from patient case records was collected in Performa’s. Results: In this study, Pulmonary TB was observed in 67.66% and extra pulmonary TB was observed in 32.33% of the individuals with the age group of 18-45 years of age being commonly affected in both Pulmonary and Extra pulmonary TB (85.02%). The mean age at the time of diagnosis was more in pulmonary TB (33.35 years) than in extra pulmonary TB (35.84 years). Males were commonly affected in pulmonary TB (57.96%) whereas females were mostly affected in extra pulmonary TB (56.48%). The mean CD4 counts in pulmonary TB were less (205.66 cells/ mm3) than extra pulmonary TB (237.65 cells/mm3) at the time of diagnosis. The mean CD4 counts and age at the time of presentation was less in female (204 cells/mm3, 30.97 years) than males in pulmonary TB which was similar to that in extra pulmonary TB in which females had a mean CD4 count of 201.08 cells/mm3 with 36.50 years as mean age. Conclusion: TB still predominates the spectrum of opportunistic infections experienced by the HIV positive individuals manifesting as either pulmonary or extra pulmonary TB. So, special emphasis should be laid in the effective implementation of preventive strategies.
Keywords: Pulmonary Tuberculosis; Extrapulmonary Tuberculosis; CD4 counts; Effective diagnosis; Opportunistic infection